Essential Oils From Five Local Plants: An Alternative Larvicide for Anopheles gambiae s.l. (Diptera: Culicidae) and Aedes aegypti (Diptera: Culicidae) Control in Western Burkina Faso - Balboné, Mahamoudou; Soma, Dieudonné Diloma; Namountougou, Moussa; Drabo, Samuel Fogné; Konaté, Hamadou; Toe, Oumarou; Bayili, Koama; Meda, Georges Benson; Dabiré, Roch Kounbobr; Gnankine, Olivier (Frontiers in Tropical Diseases, 2022)
Introduction Malaria and dengue are two main vector-borne infectious diseases transmitted by Anopheles gambiae and Aedes aegypti, respectively, in tropical and subtropical regions. The concern for environmental safety and the increasing development of resistance to the chemical in main arthropod vectors raises interest in the search for botanicals such as essential oils (EOs) that can be used in vector control. Methods Larvicidal bioassays were performed according to the WHO standard methods using Ae. aegypti and An. gambiae larvae collected from Bobo-Dioulasso and in the Kou Valley (VK), respectively, two areas located in Houet Province of western Burkina Faso. Kisumu and Bora bora, the susceptible strains of An. gambiae and Ae. aegypti, respectively, were used as controls. OEs extracted from leaves of five aromatic plants, Cymbopogon citratus, Cymbopogon nardus, Eucalyptus camaldulensis, Lippia multiflora, and Ocimum americanum, naturally growing in Burkina Faso were tested. The pyriproxyfen was used as a positive control. Results As a result, the lethal concentrations (LC50) for Ae. aegypti from Bobo-Dioulasso and An. gambiae from VK ranged from 41.9 to 103.8 ppm and 39.5 to 138.1 ppm, respectively. As for LC90 values, they ranged from 74.6 to 311.3 ppm for Ae. aegypti from Bobo-Dioulasso and from 90.2 to 328.9 ppm for An. gambiae from VK. Among the EOs tested, L. multiflora showed the highest activity against all the strains of An. gambiae and Ae. aegypti larvae. No difference in terms of LC50 values was found between L. multiflora and pyriproxyfen used as a positive control on An. gambiae larvae. It is not the case for Aedes aegypti populations, where pyriproxyfen remains the most toxic. Overall, An. gambiae populations were the most susceptible to EOs tested as compared to Ae. aegypti populations. Conclusion Our study furthers our knowledge of the larvicidal activity of EOs in the western part of Burkina and opens new avenues in their putative use in vector control strategies.